2010
DOI: 10.1128/mcb.00330-10
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Overexpression of Epitope-Tagged Mdm4 Does Not Accelerate Tumor Formation In Vivo

Abstract: Mdm2 and Mdm4 are critical negative regulators of p53. A large body of evidence indicates that elevated expression of either Mdm2 or Mdm4 may favor tumor formation by inhibiting p53 tumor suppression function. To explore this possibility in vivo, we generated conditional Mdm2 and Mdm4 transgenic mice. We show that although both transgenes are designed to be expressed ubiquitously and at comparable levels, only the Mdm4 transgenic protein is produced at high levels in vivo. In contrast, exogenous Mdm2 is consti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 53 publications
4
44
0
Order By: Relevance
“…In order to accurately do this, we developed quantitative PCR-based (qPCR-based) methods, which are illustrated in Supplemental Figure 1, A and B; supplemental material available online with this article; doi:10.1172/JCI82534DS1. As expected, whereas MDM4 protein was detectable in embryonic tissues, it was undetectable in most adult tissues, except brain, thymus, and colon (2). Remarkably, this decrease in MDM4 protein expression was accompanied by a reduced percentage spliced in (PSI), defined as the percentage of full-length Mdm4 mRNA (Mdm4-FL) over the total of all isoforms [Mdm4-FL/(Mdm4-FL + Mdm4-S)] ( Figure 1A and Supplemental Figure 1C).…”
Section: Mdm4 Is Unproductively Spliced In Most Normal Adult Tissues supporting
confidence: 84%
See 4 more Smart Citations
“…In order to accurately do this, we developed quantitative PCR-based (qPCR-based) methods, which are illustrated in Supplemental Figure 1, A and B; supplemental material available online with this article; doi:10.1172/JCI82534DS1. As expected, whereas MDM4 protein was detectable in embryonic tissues, it was undetectable in most adult tissues, except brain, thymus, and colon (2). Remarkably, this decrease in MDM4 protein expression was accompanied by a reduced percentage spliced in (PSI), defined as the percentage of full-length Mdm4 mRNA (Mdm4-FL) over the total of all isoforms [Mdm4-FL/(Mdm4-FL + Mdm4-S)] ( Figure 1A and Supplemental Figure 1C).…”
Section: Mdm4 Is Unproductively Spliced In Most Normal Adult Tissues supporting
confidence: 84%
“…An increasing body of evidence has shown that MDM4 also possesses p53-independent oncogenic functions (2,(18)(19)(20)(21). Since ASO-mediated exon 6 skipping directly affects MDM4 abundance, and not its ability to interact with p53, this approach is expected to also have an impact on the growth of MDM4-expressing, TP53-mutant melanoma cells.…”
Section: Mdm4 Is Unproductively Spliced In Most Normal Adult Tissues mentioning
confidence: 99%
See 3 more Smart Citations